Pengaruh Penggunaan Media Mind Mapping Berbasis 4C Terhadap Hasil Belajar Peserta Didik pada Pembelajaran Bahasa Indonesia Kelas V SD Negeri Tugu Jebres No.120 Surakarta Tahun Pelajaran 2022/2023 - Siti Nurhidayah; Oktiana Handini; Ani Restuningsih (Departement of Mathematics Education, 2023)
The aim of this study is to find out whether the use of 4C-based Mind Mapping media has an impact on the academic value of students of the V class of Indonesian language in SD Negeri Tugu Jebres No. 120 Surakarta teaching year 2022-2023. The total sample consisted of 29 students selected through the application of saturated sampling techniques. The data collection methodology used includes observation and testing of student learning outcomes. The observation process is carried out to assess the initial condition of the student before giving treatment, followed by a post-treatment learning assessment in the form of a double-choice test. Data analysis techniques are carried out in two ways, namely, the Preliminary Test consisting of the normality test and the Paired Sample T-test hypothesis test. The t-test uses the Paired Sample T-test. Analysing the use of the t-test formula for the Paired Sample T-test results, if the value of significance is 0,001 > 0,05, then Ho is rejected and Ha is accepted. In addition, the thitung value of 12,564 can be compared to the ttable value with dk = (N-1) so (29-1) = 28 at a 5% significance level of 2,048. If you compare thitung and ttable, then 12,564 > 2,048, which means Ho is rejected and Ha is accepted. Then the hypothesis stated that